1998
DOI: 10.1002/(sici)1521-4141(199805)28:05<1719::aid-immu1719>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

IL-10-mediated suppression of TNF-α production is independent of its ability to inhibit NFκB activity

Abstract: IL-10 has a well-characterized anti-inflammatory role that includes the suppression of inflammatory cytokine (e.g. TNF-alpha) production by monocytic/macrophage cells. Both transcriptional and post-transcriptional/translational mechanisms have been proposed to explain this process. In this study we observed that IL-10 inhibited nuclear NF kappa B DNA binding activity without affecting I kappa B degradation or translocation of NF kappa B subunits to the nucleus. While the suppression of NF kappa B in 70Z/3 pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
94
3
8

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(113 citation statements)
references
References 34 publications
8
94
3
8
Order By: Relevance
“…Previously, we have also observed IL-10-mediated inhibition of LPS-induced NF-B activity in the murine cell lines RAW 264.7 and the pre-B cell line 70Z/3. However, the concentrations required to achieve this effect were high (an IC 50 of ϳ100 ng/ml), far in excess of that required to inhibit TNF-␣ expression (an IC 50 of ϳ0.3 ng/ml) (28). However, our studies in human macrophages have failed to show any effect of IL-10 (10 ng/ml) on NF-B activation, as judged by EMSA.…”
Section: Discussionmentioning
confidence: 58%
“…Previously, we have also observed IL-10-mediated inhibition of LPS-induced NF-B activity in the murine cell lines RAW 264.7 and the pre-B cell line 70Z/3. However, the concentrations required to achieve this effect were high (an IC 50 of ϳ100 ng/ml), far in excess of that required to inhibit TNF-␣ expression (an IC 50 of ϳ0.3 ng/ml) (28). However, our studies in human macrophages have failed to show any effect of IL-10 (10 ng/ml) on NF-B activation, as judged by EMSA.…”
Section: Discussionmentioning
confidence: 58%
“…In the present study, we observed that IL-10 was produced at the time when TNF-␣ levels were beginning to decrease, and one interpretation of these data is that the effects of IL-10 on PGE 2 production are mediated by its inhibition of TNF-␣ production. It has been reported that the inhibitory effects of IL-10 on TNF-␣ production are independent of its ability to suppress the effects of NF-B activation (54,55). Studies conducted on human monocytes demonstrated that IL-10 can down-regulate surface expression of the TNF receptor while increasing production of the soluble TNF-␣ receptor, in addition to inhibiting the release of TNF-␣ itself (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the expression of the NF-jB transcription factor p65 was not affected by IL-10, nor did IL-10 impact IKB mRNA expression (Dokter et al 1996). Clarke et al (1998) found that IL-10 could not accelerate IKBa/IKBb degradation or inhibit NF-jB nuclear translocation. Clarke et al (1998) speculated that there must be some other mechanism besides IKB degradation and DNA combination.…”
Section: Discussionmentioning
confidence: 93%
“…The degradation of IjB is necessary for the translocation of NF-jB to the nucleus and subsequent binding to DNA. IKK plays a role in the phosphorylation and degradation of IjB (Clarke et al 1998;Hovsepian et al 2013). We next examined IjB and the phosphorylation of IKKa/b in these cells by Western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation